Nociplastic pain: the prominent role of non-neuronal cells in central and peripheral sensitization - Lai, Weidong; Tang, Xin; Chen, Sijia; Zhou, Yihan; Qi, Zihan; Cao, Menglei; Yuan, Cunrui; Yu, Jie; Wen, Chengping (Frontiers in Immunology, 2026)
Nociplastic pain (NPP) is a recently defined form of chronic pain, characterized by altered nociception in the absence of clear evidence of nociceptive or neuropathic pain. It is believed to be driven by maladaptive changes in nociceptive processing, mediated by the peripheral and/or central nervous system sensitization. However, the exact pathogenic basis for NPP initiation and development remains unclear, and the potential clinical manifestations and biomarkers lack a clear classification. Emerging evidence now emphasizes the role of complex neuron–non-neuronal cell interactions, highlighting non-neuronal cells (e.g., circulating immune cells and glial cells) in NPP pathogenesis. In this review, we delineate the key conceptual distinctions of NPP within the spectrum of chronic pain and present the latest evidence outlining how non-neuronal cells mediate NPP progression via peripheral and central sensitization, as well as the associated synaptic plasticity mechanisms. We also summarize current and experimental therapeutic approaches explored in preclinical and clinical studies of NPP. We hope that this review provides a theoretical foundation for subsequent analgesic target screening and the drug development for NPP.